PENINGKATAN PRODUKTIFITAS PADA PENGRAJIN COR KUNINGAN DI DESA BEJIJONG, TROWULAN MELALUI PERBAIKAN DESAIN FASILITAS KERJA - Peniel Gultom; Dwi Anggorowati; Sanny Andjarsari (Prodi Teknik Industri S1 Institut Teknologi Nasional Malang, 2014)
Bejijong Village, Trowulan, Mojokerto is a tourist village and small industrial centers of handicraft cast brass. The product is a range of miniature statues, temples, statues of figures Majapahit kingdom and etc which using the waste of metal as a raw material. Cast brass handicrafts is also becoming one of the flagship products typical souvenir Mojokerto - East Java. There are currently about 125 entrepreneurs cast brass with a total of 648 people craftsmen. In the manufacture of cast brass handicrafts craftsmen still use traditional furnace to melt various metal waste such as petromaks, bolts, nuts, hinges etc. as raw material. The diesel-fueled furnaces and wood charcoal. In the smelting process 50 kg of molten metal waste spend 25 liters of diesel fuel for about 4 hours. Difficulties faced by craftsmen is when it was about to pour must first dismantle furnace wall while the fire from brander only burn the bottom of furnace with open conditions. It can not achieve the maximum heat so that melting process becomes longer resulting in wasted fuel. Seeing the conditions above then IbM team from ITN Malang designing a Metal Waste Fuser Tool by applying portable appropriate technology which can makes it easy the process of working and can saving time and fuels. The results obtained are a metal waste fuser tool that efficiently and effectively in terms of the size, shape, ways of working and saving fuels. Once foundries 50 kg of liquid metal waste spend one 12 kg LPG tube for about 2 hours.